TECHNOLOGY-BASED TEACHING STRATEGIES IMPLEMENTED BY ENGLISH TEACHERS BEFORE AND DURING COVID-19 IN EFL CONTEXT - Aminah Aminah; Nurwahida Nurwahida; Nurmawati Nurmawati (elstic : english language linguistics culture, 2021)
This study aimed at finding out the technology-based teaching strategies implemented by English teachers in teaching English before and during COVID-19. This study applied a qualitative design with a case study approach. The participants were two English teachers of SMP Negeri 3 Galesong Utara. The data were collected by using interview and documentation, and they were analyzed by using Miles and Huberman’s theory consisting of three steps: data reduction, data display, and conclusion/ verifying.  Furthermore, it was revealed from the study that before COVID-19, the teachers applied discovery learning, inquiry strategy, problem based learning teaching, contextual teaching strategies and interactive teaching in which they applied some technologies such as Internet, wireless speaker Bluetooth, PPT, and LCD in offline class. Meanwhile during COVID-19, the teachers implemented the lecture model through virtual classes, and monitored students and videos of discussions related to the material through WhatsApp, video conference, and by using self-made videos in which the teachers used technologies such as internet, smartphones, laptops, Zoom, Google Classroom, WhatsApp, Online Dictionary, and YouTube. The inhibited factors encountered by teachers before COVID-19 were intake or the reasoning ability, students thinking power which were still lacking, and extended time space for English lessons in class. While during COVID-19, the subdued factor was that students have difficulty in focusing and concentrating during teaching process, difficulty in accessing applications, smartphones and laptops that suddenly went error due to unstable signals. It is suggested that technology-based teaching strategies applied by the teachers should be adjusted with the conditions of the students, and it is pivotal to strengthen teachers’ mastery in technology to attract the students in ELT process.